1996
DOI: 10.1055/s-2008-1071031
|View full text |Cite
|
Sign up to set email alerts
|

The Cost of Preventable Conditions in Adults with Spina Bifida

Abstract: Adults with spina bifida are at risk of developing secondary health conditions that are causally related to the primary condition and are to some degree preventable. By investigating preventable secondary conditions in adults with spina bifida, we can determine the burden of care that might be reduced if preventive strategies were developed. We audited hospitalizations of adults with spina bifida to gain insight into serious secondary conditions in this population. We reviewed all admissions of adults with spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(54 citation statements)
references
References 0 publications
2
51
0
1
Order By: Relevance
“…Although no single study has captured all the direct and indirect costs associated with this serious disability, the burden is believed to be in the millions of dollars throughout the life of the individual (11)(12)(13)(14). Our study has identified a previously unrecognized group of women who are at high risk for NTD should they become pregnant, namely women of childbearing age who have low red cell folate and may only become aware of it while a test for folate is conducted in the process of exploring the causes for their anemia.…”
Section: Discussionmentioning
confidence: 99%
“…Although no single study has captured all the direct and indirect costs associated with this serious disability, the burden is believed to be in the millions of dollars throughout the life of the individual (11)(12)(13)(14). Our study has identified a previously unrecognized group of women who are at high risk for NTD should they become pregnant, namely women of childbearing age who have low red cell folate and may only become aware of it while a test for folate is conducted in the process of exploring the causes for their anemia.…”
Section: Discussionmentioning
confidence: 99%
“…Este mismo autor cifra la litiasis renal en concreto en el 6,1%, apreciando un aumento del riesgo de la misma con el paso de los años. -lesión única pura -1 (1,9) -no valorable 1 (10) 7 (13,4)…”
Section: Discussionunclassified
“…NTD births constitute considerable social and economic burden for the affected families and the health system [11]. The lifetime hospital admissions because of secondary conditions is markedly higher in patients with spina bifida compared to healthy individuals [12]. The relative risk (RR) of death among children with spina bifida is higher compared to children without birth defects [13].…”
Section: Timely Supplementation Of Folate Prevents Birth Defectsmentioning
confidence: 99%